An Economic Analysis of Chia Cultivation in Kalyan Karnataka Region - , Shiva Kumar; , Jainuddin S M; , Amrutha T Joshi; , Vasudeva Naik; , A S Police Patil (Archives of Current Research International, 2025)
Chia (Salvia hispanica L.) is gaining prominence as a superfood and medicinal plant within the Lamiaceae family, celebrated for its pseudocereal status and nutritional benefits worldwide. Introduced to India by the Central Food Technological Research Institute (CFTRI) in Mysuru, it has swiftly spread across the country, including Karnataka's Kalyan-Karnataka region, owing to its rich nutritional profile and medicinal properties. This study delved into the cost and returns structure of chia cultivation, focusing on Bidar and Kalaburagi districts, which are pivotal due to their significant chia cultivation areas. Primary data was gathered through surveys of 30 sample farmers from each district during the 2023-24 period, totalling 60 samples. The findings revealed that chia cultivation in Bidar was marginally more profitable compared to Kalaburagi, evident from higher net returns. However, the returns per rupee invested were superior in Kalaburagi. The net returns over total costs stood at Rs 22652.50 and Rs 23755.40 per acre in Bidar and Kalaburagi respectively, with benefit-cost ratios of 2.46 and 2.61. Productivity per acre slightly favoured Bidar at 3.11 quintals compared to Kalaburagi 3.08 quintals, due to better water management practices and proper adoption of technology by the farmer. Overall, chia cultivation in these districts showcases promising economic viability and productivity, highlighting its potential as a lucrative crop for farmers in the region.